Understanding Women’s Rights according to Barbare Jorjadze - Bandzeladze, Manana; Chkhirodze, Darejan (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2021)
Barbare Jorjadze is one of the best representatives of Georgian culture. Her work in literary and public activities is noteworthy. Particularly noteworthy is her role in the field of women’s rights and education. She is distinguished by fairness, directness and sincerity. These qualities allowed her to use her full potential and not only helped to establish herself, but also to change the status of disenfranchised women. We are especially interested in her works on women’s rights and education. She has dedicated a number of papers to this topic. Her letter „A few words for the attention of young men“ is important. She boldly touched on the disenfranchised status of women and noted that the reason for this is poor upbringing and environmental conditions. Girls were instructed from birth that they should be silent and they had less right to education. That low level of education is a result of a lack of awareness of women. It can be said that Barbare Jorjadze is the first Georgian woman by whom gender-feminist ideas were voiced. The new understanding of women’s rights was met with hostility by much of society, especially men. However, she was not afraid of such challenges and boldly defended her own opinion. The first culinary book created by Barbare Jorjadze is noteworthy, where not only Georgian but also European dishes are given. In this way, she contributed to bringing Georgian and European cultures closer. She played a major role in the development of women’s economic, social, civil, political, and cultural rights.